DATA CONCENTRATION UNIT HAVING ELECTRIC VEHICLE CHARGING AND METHOD USING THE SAME - SEO MIN HO; JUNG JOON HONG; JUNG SU MI (2021)
The present invention relates to a data concentration apparatus installed on an electric pole to communicate with a consumer side smart watt-hour meter and a power supplier in order to embody an intelligent power network. The data concentration apparatus includes: a communication interface part providing a communication interface with a server storing member information of members subscribing to an electric vehicle charging service using the data concentration apparatus and performing authentication and billing processing for the provision of the service based on the member information; a charging part including a connector connected with a charging terminal of the electric vehicle, and charging the electric vehicle in response to the combination of the connector and the charging terminal of the electric vehicle; and a charging control part controlling the charging part by receiving service authentication information from the server through the communication interface part, thereby performing an electric charging function. Therefore, the present invention has advantages of solving difficulty in place selection for the installation of an electric vehicle charging station, preventing the incurrence of additional costs for charger supply and easily bringing power. Moreover, the present invention has an advantage of securing an electric pole and a parking space as electric vehicle charging spaces to enable an electric vehicle driver to easily find a charger, and easily charge an electric vehicle. 본 발명은 지능형 전력망을 구현하기 위해 전주에 설치되어 수용가측 스마트 전력량계 및 전력 공급자와의 통신을 수행하는 데이터 집중 장치에 있어서, 상기 데이터 집중 장치를 이용한 전기차 충전 서비스를 이용하기 위해 회원으로 가입한 회원들의 회원정보를 저장하고 상기 회원정보에 의거하여 상기 서비스 제공을 위한 인증 및 과금처리를 수행하는 서버 장치와의 통신 인터페이스를 제공하는 통신 인터페이스부; 전기차의 충전단자와 연결되는 커넥터를 포함하고, 상기 커넥터와 전기차의 충전단자의 결합에 응답하여 상기 전기차를 충전하는 충전부; 및 상기 통신 인터페이스부를 통해, 상기 서버장치로부터 서비스 인증 정보를 전달받아 상기 충전부를 제어하는 충전제어부를 포함하여, 전기차 충전 기능을 수행한다. 따라서, 본 발명은 전기차 충전소 설치를 위한 입지 선정의 어려움을 해소하고, 충전기 보급을 위한 추가 비용이 발생하지 않으며 전력을 쉽게 가져다 쓸 수 있는 장점이 있다. 또한, 본 발명은 전주 및 주차공간을 전기차 충전 공간으로 확보하여 전기차 운전자가 보다 쉽게 충전기를 찾을 수 있고, 용이하게 전기차를 충전할 수 있도록 하는 장점이 있다.